2022
DOI: 10.1186/s12913-022-08690-z
|View full text |Cite
|
Sign up to set email alerts
|

The reimbursement for expensive medicines: stakeholder perspectives on the SMA medicine nusinersen and the Dutch Coverage Lock policy

Abstract: Background The reimbursement for expensive medicines poses a growing challenge to healthcare worldwide. In order to increase its control over the costs of medicines, the Dutch government introduced the Coverage Lock (CL) policy in 2015. The CL postpones decisions regarding reimbursement of expensive medicines until detailed advice on i.e., cost-effectiveness has been given. The CL has been in place for six years, has raised many questions and concerns, but currently, no evaluation is known to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Both the call to use the models strategically to accelerate the CL-procedure and the call for more transparency regarding the CL-procedure stemmed from dissatisfaction with some aspects of the current CL-procedure. Criticism of the lack of transparency and the duration of the CL-procedure has also been found by Scheijmans et al, in their study on the experiences of stakeholders during the CL-procedure of Nusinersen (Scheijmans et al, 2022). The lack of transparency is problematic from the perspective of procedural justice.…”
Section: Call For Strategic Action and Transparencymentioning
confidence: 94%
See 1 more Smart Citation
“…Both the call to use the models strategically to accelerate the CL-procedure and the call for more transparency regarding the CL-procedure stemmed from dissatisfaction with some aspects of the current CL-procedure. Criticism of the lack of transparency and the duration of the CL-procedure has also been found by Scheijmans et al, in their study on the experiences of stakeholders during the CL-procedure of Nusinersen (Scheijmans et al, 2022). The lack of transparency is problematic from the perspective of procedural justice.…”
Section: Call For Strategic Action and Transparencymentioning
confidence: 94%
“…However, it is unclear for how many patients or in how many hospitals access was possible. A previous interview study amongst a diverse group of Dutch stakeholders regarding access to Nusinersen while it was in the lock, showed that stakeholders perceived the time which treatments spent in the lock to be too long ( Scheijmans et al, 2022 ). Another interview study amongst Dutch physicians showed that physicians sometimes encounter problems when they want to prescribe treatments which are in the CL ( Bomhof et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…• Scheijmans et al 2022 (38) : estudio realizado con datos procedentes de un registro de pacientes con AME tratados con nusinersén en Países Bajos. Se estudiaron a 69 pacientes (23, 30 y 16 con AME tipo I, II y III, respectivamente) en los que el inicio precoz del tratamiento se asoció a una mejor respuesta (p<0,001) en la consecución de hitos motores.…”
Section: Figura 2 Terapias Avanzadas En La Atrofia Muscular Espinalunclassified